Patients with community-acquired bacteremia of unknown origin: clinical characteristics and usefulness of microbiological results for therapeutic issues: a single-center cohort study - Johan Courjon; Elisa Demonchy; Nicolas Degand; Karine Risso; Raymond Ruimy; Pierre-Marie Roger (BMC, 2017)
Abstract Bacteremia of unknown origin (BUO) are associated with increased mortality compared to those with identified sources. Microbiological data of those patients could help to characterize an appropriate empirical antibiotic treatment before bloodcultures results are available during sepsis of unknown origin. Based on the dashboard of our ward that prospectively records several parameters from each hospitalization, we report 101 community-acquired BUO selected among 1989 bacteremic patients from July 2005 to April 2016, BUO being defined by the absence of clinical and paraclinical infectious focus and no other microbiological samples retrieving the bacteria isolated from blood cultures. The in-hospital mortality rate was 9%. We retrospectively tested two antibiotic associations: amoxicillin-clavulanic acid + gentamicin (AMC/GM) and 3rd generation cephalosporin + gentamicin (3GC/GM) considered as active if the causative bacteria was susceptible to at least one of the two drugs. The mean age was 71 years with 67% of male, 31 (31%) were immunocompromised and 52 (51%) had severe sepsis. Eleven patients had polymicrobial infections. The leading bacterial species involved were Escherichia coli 25/115 (22%), group D Streptococci 12/115 (10%), viridans Streptococci 12/115 (10%) and Staphylococcus aureus 11/115 (9%). AMC/GM displayed a higher rate of effectiveness compared to 3GC/GM: 100/101 (99%) vs 94/101 (93%) (p = 0.04): one Enterococcus faecium strain impaired the first association, Bacteroides spp. and Enterococcus spp. the second. In case of community-acquired sepsis of unknown origin, AMC + GM should be considered.